The misadventures of Dolt & Aura (Raton, New Mexico G. O, Productions)
Developed and connected with the Literacy Program
1 Pamplet of the play Dolt and Aura by Gerald C. Ortiz
Master list item #32
File location is in the Raton File Cabinet drawer 3
Keywords: Library -- 2 copies. -- Raton, New Mexico; Coker, Jonnie -- Scenic Designer; Ortiz, Gerald C. -- Director; Cornay, Catherine -- Narrator; Menapace, Tonya -- Princess Aura; Ortiz, Gerald C. -- Knight Dolt; Play; Brahma, Chris -- Lord Decipher; Swanson, Sharon L. -- Lady Decipher; Barreras, Chuck -- King Scholarly; Coker, Jonnie M. G. -- Queen Scholarly; Gonzales, Robi -- Wizard